A foreign body in the soft tissues after molar tooth extraction as an iatrogenic complication - a case report - Stelmach, Rafał; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes a case of iatrogenic complication as a result of the 26 tooth extraction in 50 year old female patient.